Quantitative monitoring of the removal of non-encapsulated material external to filled carbon nanotube samples. Issue 47 (11th November 2015) - Martincic, Markus; Pach, Elzbieta; Ballesteros, Belén; Tobias, Gerard
Abstract : UV-Vis spectroscopy has been employed to monitor the removal of non-encapsulated external material from samples of filled carbon nanotubes. Abstract : The endohedral functionalization of carbon nanotubes with both organic and inorganic materials allows the development of tailored functional hybrids whose properties benefit from the synergistic effects of the constituent compounds. Bulk filling of carbon nanotubes (CNTs) results in samples that contain a large amount of non-encapsulated material external to the CNTs. The presence of the external material is detrimental to the processing and application of the resulting hybrids. Here we introduce the use of UV-Vis spectroscopy to monitor the cleaning process, i.e. the elimination of non-encapsulated compounds. Chrome azurol S has been employed to assess the bulk removal of external samarium(iii ) chloride from filled single-walled carbon nanotubes. Chrome azurol S is of interest since it can be used to quantify a large variety of materials in a fast, accurate and reliable manner. The parameters that control the cleaning process have been optimized, including the time, temperature, volume and sonication, to achieve a fast and complete removal of the external material.